Materials under extreme conditions recent trends and future prospects - Tyagi, A. K.; Banerjee, S. (Amsterdam, Netherlands Elsevier, 2017)
Materials Under Extreme Conditions: Recent Trends and Future Prospects analyzes the chemical transformation and decomposition of materials exposed to extreme conditions, such as high temperature, high pressure, hostile chemical environments, high radiation fields, high vacuum, high magnetic and electric fields, wear and abrasion related to chemical bonding, special crystallographic features, and microstructures. The materials covered in this work encompass oxides, non-oxides, alloys and intermetallics, glasses, and carbon-based materials. The book is written for researchers in academia and industry, and technologists in chemical engineering, materials chemistry, chemistry, and condensed matter physics.--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Materials -- Testing; Materials at high pressures; Materials at high temperatures; Materials at low temperatures; Electronic books